SULFUR ELECTRONIC ENVIRONMENTS IN αNIS AND β-NIS: EXAMINATION OF THE RELATIONSHIP BETWEEN COORDINATION NUMBER AND CORE ELECTRON BINDING ENERGIES - Goh S.W.; Buckley A.N.; Lamb R.N.; Skinner W.M.; Pring A.; Wang H.; Fan L.J.; Jang L.Y.; Lai L.J.; Yang Y.W. (My University, 2006)
X-ray photoelectron spectra have been obtained under the same experimental conditions for synthetic α-NiS and natural β-NiS in order to establish any difference in S electronic environment, and to test the proposition that S core electron binding energies increase measurably with coordination number when the same metal is in different sulfide structures or lattice sites. The Ni and S electronic environments in the two NiS structures have been further probed by near-edge X-ray absorption fine structure (NEXAFS) spectroscopy, and the NEXAFS spectra interpreted by reference to spectra simulated by ab initio calculations. The photoelectron and NEXAFS spectra for freshly prepared surfaces of α-NiS and β-NiS were found to be similar, with only subtle differences in electronic environment evident in the experimental and simulated NEXAFS spectra. The measured and calculated core electron binding energies did not support the previously postulated relationship between S coordination number and electron binding energies. © Springer-Verlag 2006.
Keywords: α-NIS; MILLERITE; NEXAFS; XPS